Correlation of Cardiopulmonary Bypasses and Cardiac Troponin I in Predicting Post-Op Arrhythmia - Afzal Qasim, Masroor Hussain Sharfi, Ibtesam-E-Fajar, Riffat Farrukh, Shahida Mushtaq, Aummara Rafique, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The correlation of cardiopulmonary bypasses (CPB) and cardiac troponin I (cTnI) in predicting arrhythmia remain unclear. Aim of this study to investigate the correlation of cardiopulmonary bypasses duration and cardiac troponin I with the type of arrhythmias. Methods: This is a retrospective observational study took place in our hospital between May 2020-December 2021.The study included a total of thirty-three patients who underwent open-heart surgery. Patients between the age of 2 months and 14 years of both genders with the diagnosis of ventricular septal defect (VSD), atrioventricular defect (AVSD) and tetralogy of Fallot (TOF) were included in this study. Patients with preoperative a history of major intraoperative events and high-level of cardiac troponin I were excluded from the study. The accuracy was calculated using sensitivity and specificity. The area under the ROC curve (95% CI) and p-value were also calculated. Results: Out of thirty-three patients undergoing open-heart surgery, 58.1% were male and were one year of age or more (71%). A statistically significant correlation among arrhythmia, cardiac troponin I and cardiopulmonary bypasses was observed (p < 0.05). Cardiac troponin I predicted high-level sensitivity for arrhythmias, hospital stay, and intensive care unit stay, while low specificity was reported for cardiac troponin I compared to cardiopulmonary bypasses. Conclusion: The higher level of cardiac troponin I was correlated with the underlying burden of arrhythmias. A novel high- sensitivity cardiac troponin I assay can protectively recognize patients at low risk of arrhythmias. Keywords: Arrhythmia, Cardiac troponin I, Cardiopulmonary bypass, Sensitivity, Specificity